Fluid inclusions study of Cu-rich deposits from Sousel-Barrancos metallogenic belt (Ossa-Morena Zone, Portugal) - MAIA, Miguel (2020)
The physical and chemical properties of mineralising fluids may provide important input for the metallogenic modelling of a particular deposit. The purpose of this study is to characterise the fluids involved with Cu mineralisation in the Miguel Vacas and Mociços ancient mines, as well as the Ferrarias occurrence, located in the Portuguese Ossa-Morena Zone (OMZ), in the denominated Sousel-Barrancos metallogenic belt (SBMB). These deposits are characterised by quartz + carbonate veins with main sulphide mineral assemblages of chalcopyrite + pyrite and bornite ± digenite in the supergene enrichment zone. In Ferrarias, sphalerite and galena were also identified, whereas arsenopyrite was found in the Miguel Vacas deposit. The evaluation of relative ages and spatial distribution of fluid inclusions is essential for establishing a metallogenic model for these Cu-rich deposits. Twenty bipolished thick sections were prepared from borehole and surface samples, and over 400 fluid inclusions (FI´s) were studied using microthermometry and Raman spectroscopy.